2004
DOI: 10.1136/gut.53.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Lysine kinetics in preterm infants: the importance of enteral feeding

S R D van der Schoor

Abstract: Introduction: Lysine is the first limiting essential amino acid in the diet of newborns. First pass metabolism by the intestine of dietary lysine has a direct effect on systemic availability. We investigated whether first pass lysine metabolism in the intestine is high in preterm infants, particularly at a low enteral intake. Patients and methods: Six preterm infants (birth weight 0.9 (0.1) kg) were studied during two different periods: period A (n = 6): 40% of intake administered enterally, 60% parenterally; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
3
25
0
1
Order By: Relevance
“…The background (baseline) values of the 13 C label in expiratory air did not differ between the two study days (study d 1: 1.0997 Ϯ 0.0036 and study d 2: 1.0956 Ϯ 0.0001 APE; p ϭ 0.3) and were in the same range as we have found previously (8,20). Similarly, baseline enrichments of [U- 13 (6,8). To determine splanchnic and whole body glutamine kinetics, we used plateau glutamine enrichment values from plasma and labeled carbon dioxide in expiratory air (Tables 2 and 4).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The background (baseline) values of the 13 C label in expiratory air did not differ between the two study days (study d 1: 1.0997 Ϯ 0.0036 and study d 2: 1.0956 Ϯ 0.0001 APE; p ϭ 0.3) and were in the same range as we have found previously (8,20). Similarly, baseline enrichments of [U- 13 (6,8). To determine splanchnic and whole body glutamine kinetics, we used plateau glutamine enrichment values from plasma and labeled carbon dioxide in expiratory air (Tables 2 and 4).…”
Section: Resultssupporting
confidence: 70%
“…A similar finding was observed in preterm infants regarding glutamate oxidation. Almost 90% of the used glutamate in the first pass was oxidized, while essential amino acids such as leucine and lysine were not oxidized in preterm infants (6). Furthermore, glucose oxidation (10 kcal ⅐ kg Ϫ1 ⅐ d Ϫ1 ) contributed five times as much as glutamate oxidation (1.7 kcal ⅐ kg Ϫ1 ⅐ d Ϫ1 ) to splanchnic CO 2 production, indicating that glucose is the major source of energy in the human neonatal intestine (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans also show considerable intestinal amino acid metabolism (4,5) and the metabolic rate is even higher in preterm infants. Previous studies showed that first-pass metabolism of leucine in newborns is twice that of adults (6) and that in preterm infants, a great amount of dietary lysine is used in first pass as well (7).…”
mentioning
confidence: 99%